Composition of the collection of primitive cultivated species within the Solanum L. section Petota Dumort. and contemporary trends in their research - E. V. Rogozina; A. A. Gurina (Труды по прикладной ботанике, генетике и селекции)
The diversity of potato genetic resources in the VIR genebank harbors one of the world’s first collections of primitive cultivated species. These accessions are native potato varieties cultivated by the indigenous population of South America. The oldest accessions in the collection are traced back to 1927. Approximately one fifth of the collection (106 accessions out of 573) is the unique material procured by VIR’s collecting missions to Bolivia, Colombia, Ecuador, and Peru. According to S. Bukasov’s potato classification, the diversity of South American highland potatoes explored by VIR’s collectors belongs to spp. Solanum ajanhuiri Juz. et Buk., S. × chaucha Juz. et Buk., S. mammilliferum Juz. et Buk., S. phureja Juz. et Buk., S. rybinii Juz. et Buk., S. goniocalyx Juz. et Buk., S. stenotomum Juz. et Buk., S. tenuifilamentum Juz. et Buk., S.× juzepczukii Buk., and S. × curtilobum Juz. et Buk. Within this group of species, S. × ajanhuiri, S. phureja and S. stenostomum are the closest in their characteristics to ancient domesticated forms of tuber-bearing Solanum spp. This publication is an analytical review of the current composition of the primitive cultivated potato species collection and the results of its earlier studies. Ecogeographic descriptions of the sites native for cultivated potatoes and information on the sources of the accessions are presented. A large-scale evaluation of primitive cultivated potato accessions by a set of characters, carried out in field and laboratory experiments, uncovers their breeding potential and serves as the primary information platform for further indepth research. Studying S. phureja and closely related cultivated potato species is important for finding solutions of fundamental problems in plant biology. The data arrays accumulated today would facilitate targeted selection among accessions to identify most promising ones for molecular genetic studies into the gene pool diversity of potato species.